Understanding barriers to access and utilization of cervical cancer screening services among women living with HIV in Kyenjojo District, Western Uganda protocol - Wycliff, Katwesige; Daniel, Ebenezer (My University, 2018)
Introduction Cervical Cancer is preventable and ranks as the second common cancer among women globally. Since 1981, the incidence of cervical cancer has been on the rise among women living with HIV/AIDS. Cervical cancer in Uganda is usually diagnosed late and the prognosis is very poor. There are gaps in general knowledge on cervical cancer (CC) screening and availability of screening services in the country. This study is intended to explore such barriers to access and utilization of cervical cancer screening services among WHIV in Kyenjojo District Methodology We will search publications and written articles on cervical cancer prevention especially screening among HIV women, from PubMed, Cochrane libraries, as well as the ministry of health unpublished reports. We will employ a qualitative study design using key informant (KI) purposively selected from Kyenjojo Hospital Reproductive Health and ART Clinics. This will permit us to achieve a detailed investigation using health belief model on individual perceptions while providing deeper insights into the factors that hinder access and utilization of cervical cancer screening services among HIV/AIDS women in Kyenjojo District. Conclusion This study is intended to explore such barriers to access and utilization of cervical cancer screening services among WHIV in Kyenjojo. The study will thus significantly contribute to improved programming, advocacy, and efforts to scale up CC services among rural populations in Uganda while contributing to overall maternal survival in line with 2030 Sustainable Development Goals country initiatives
Supplemental Materials: https://osf.io/z9r6u/
Keywords: access; Barriers; Cervical Cancer; Grounded Theory; HIV; Kyenjojo Uganda; Protocol; Screening; Utilisations; Women